Financial management - Johnson, Robert Willard (Allyn and Bacon, 1966)
This book is designed to achieve a specific objective for a certain group of readers. The objective is to provide a theoretical or conceptual framework that a financial manager can use to reach decisions in the real world. The book is intended to serve the reader who is studying the field of financial management for the first time; nevertheless, while the text is not a learned treatise designed to parade mathematical models and theoretical controversies before budding doctoral students, many advanced students and practitioners may find it useful for reviewing major trends in theory and application. . . .